WebQuest (Journal of Parents and Teachers, 2014)
It is interesting that we begin to use WebQuest as tools to improve the quality of the teaching and learning process. This article explains the steps to take before starting to make a WebQuest: choose topic, put a title, specify areas, and types of learning. A computer program for chemical work is also offered.
Keywords: WebQuest; ICT; teachers 3.0; chemistry.